Hydrogen production by dark fermentation using a new low-cost culture medium composed of corn steep liquor and cassava processing water: Process optimization and scale-up. (January 2021) - Martinez-Burgos, Walter José; Sydney, Eduardo Bittencourt; de Paula, Dieggo Rodrigues; Medeiros, Adriane Bianchi Pedroni; de Carvalho, Júlio Cesar; Molina, Denisse; Soccol, Carlos Ricardo
Graphical abstract: Highlights: Agroindustrial wastes were combined into a low-cost medium for biohydrogen production. Good biohydrogen productivity was reached without the addition of chemicals. Corn steep liquor and cassava processing water medium-cost was as low as 81.5/m 3. Medium costs were 80% lower than those reported in the literature. Scaled-up production of biohydrogen resulted in increased yields, up to 40% higher. Abstract: The use of effluents for hydrogen production through dark fermentation is promising because it results in the generation of value-added products and reduction of the effluent's organic load. A low-cost medium using agroindustrial effluents, corn steep liquor (CSL) and cassava processing wastewater (CPW) was evaluated for hydrogen production with microbial consortia ( Vir and Gal ). Four variables were evaluated for their impact on biohydrogen production through a Plackett Burman design. Subsequently, the significant variables were optimized using a central composite design, resulting in two mathematical models with regression coefficients R 2 > 0.92. The maximum yields were validated and resulted in 107 and 83.1 mL of biohydrogen/g COD removed for Vir and Gal, respectively. The lower medium cost for biohydrogen production was 81.5 USD/m 3, approximately 80% more economical than some supplemented media. Finally, the scale-up of the biohydrogen production by consortia to 5L resulted in an increase of more than 40%.